Vegetal Lung Route: Identification, characterization and assessment of agroecological tourism resources - Fernández, Alfonso José (2025)
This study addresses the need for a sustainable tourism model that combines agroecology and cultural heritage in the Ezequiel Zamora Botanical Garden, Alto Barinas Parish, Barinas Municipality, Venezuela. The purpose is to identify, characterize, and value agroecological and heritage tourism resources to design a sustainable route that benefits visitors and the local community. A qualitative participatory approach was used, revealing a territory with agricultural, natural, and cultural potential, although the lack of infrastructure and limited community integration are key challenges to developing a sustainable tourism route. It is concluded that, to diversify the agroecological tourism offering and foster sustainable development, it is essential to empower the community, overcome limitations in participation, and strengthen tourism infrastructure, promoting a holistic approach that integrates socioeconomic benefits and heritage conservation.